Chapter Opportunities of Circular Economy in a Complex System of Woody Biomass and Municipal Sewage Plants - Attila, Bai (InTechOpen, 2021)
In this chapter, we present the opportunities and general importance of woody biomass production (forests and short-rotation coppices) and waste management in a common system. Wastewater and different forms of sewage sludge, as energy- and nutrient-rich materials, can contribute to reaching resource efficiency, savings in energy, and reduction of CO2 emissions. Within certain limits, these woody plantations are suitable options for the environmentally sound disposal of wastewater and/or sewage sludge; in addition, they can facilitate the realization of full or partial energy self-sufficiency of the wastewater plant through bioenergy production. Focusing on circular economy, we introduce the aspects of the treatment process and the sizing issues regarding the municipal wastewater treatment and the woody biomass in a complex system. Based on a specific case study, approximately 826 ha of short-rotation coppices (with a 2-year rotation) are required for the disposal of sewage sludge generated by a 250,000 population equivalent wastewater treatment plant. If we look at the self-sufficiency of its energy output, 120-150 ha of short-rotation coppices may be adequate. This complex system can replace the emissions of around 5650 t of CO2 through electricity generation alone and another 1490 t of CO2 by utilizing the waste heat.